THE INNOVATIVE ADMINISTRATION DEVELOPMENT OF SRAKAEW SUB-DISTRICT ADMINISTRATIVE ORGANIZATION, PHETCHABUN PROVINCE - Lueacha, Thidarak (Academic Journal Phranakhon Rajabhat University, 2022)
This research aimed to study on 1) the problems of administration according to the mission of the Sra Kaeo Subdistrict Administrative Organization and 2) to develop the innovative administration of the Sra Kaeo Subdistrict Administrative Organization. This research is a qualitative research. Collect information about problems of administration according to the mission of the Sra Kaeo Subdistrict Administrative Organization by in-depth interview. The group of key informants totaled 7 people and The innovative administration of Sra Kaeo Subdistrict Administrative Organization developed by group discussion by 6 key informants. The research result found that 1) The administrative problem of Sra Kaeo Subdistrict Administrative Organization were shortage of personnel in operation , problems of budget and insufficient materials and equipment for operation. 2) Innovative administration consists of innovation in human resource cooperation with nearby local government organizations. Fiscal innovations include expanding the land and construction tax base. Providing private investment and renting space for building a community distribution center or a food court for tourist services and collecting fees from visiting.